(untitled) (Edad Media. Revista de Historia, 2024)
Based on seven chronicles written in Sicily and the Crown of Aragon between the end of the 13th century and the second third of the 14th century, this article examines how the chroniclers include diplomatic work, negotiations and acts leading to peace in their accounts of the conflict following the Sicilian Vespers. Diplomatic exchanges are a facet of a wider conflict, sometimes amplifying it; their realization is a real test for protagonists desirous of peace and doubtful of the enemy’s sincerity. If peace often seems impossible, two main ways out of the cycle of conflict emerge: divine grace, the dispenser of a good peace; and agreements based on mutual concessions and mercy.